Unveiling the hidden connection: Investigating the relationship between shared leadership and missed nursing care - Amal Diab Ghanem Atalla; Naglaa Abdelaziz Mahmoud Elseesy; Ayman Mohamed El-Ashry; Samia Mohamed Sobhi Mohamed; Ebaa Marwan Felemban; Abdulhafith Alharbi; Nervana Abdelrahman Saied Gheith; Sabrein Mahmoud khalifa khattab (International Journal of Nursing Sciences)
Objectives: This study examined the levels of shared leadership and missed nursing care and their relationship among nurses in Egypt. Methods: A cross-sectional survey was conducted. From February to April 2024, 340 nurses worked in all inpatient care units at Alexandria Main University Hospital. The Shared Leadership and Missed Nursing Care Survey was used for evaluation. Results: The overall score of shared leadership was (72.62 ± 4.30), which imitates a high perception of shared leadership among nurses; the dimension of delegation achieved the highest average mean score (3.66 ± 0.26), followed by collaboration (3.64 ± 0.31), the vision dimension scored the lowest mean score (3.59 ± 0.33). The elements of missed nursing care had a total score of (46.72 ± 5.69), and the dimension of secondary care achieved the highest average mean score (3.74 ± 0.31). The reasons for missed nursing care had a total mean score of (22.40 ± 1.59), and the dimension of labor resources achieved the highest average mean score (3.20 ± 0.22). Male nurses, less than 30 years old, married, held a bachelor’s degree in nursing sciences, less than five years of experience in the nursing profession, and less than five years of experience in the current working unit had higher total scores of the shared leadership and lower total scores of missed nursing care (P < 0.001). A negative correlation existed between shared leadership and two dimentisons (the elements of nursing care [r = −0.383], the reasons for missing nursing care [r = −0.047]) (P < 0.001). Conclusions: The study’s findings can help as a theoretical underpinning for nursing leaders to stand in an environment that reduces the incidence of missed nursing care by encouraging teamwork, responsibility, workload management, and empowerment among nurses.